2023
DOI: 10.1021/acs.jnatprod.3c00087
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Neuroinflammatory Meroterpenoids from a Chinese Collection of the Brown Alga Sargassum siliquastrum

Abstract: Nine new chromane-type meroterpenoids, including the rare nor-meroterpenoid sargasilol A (1) and the eight meroditerpenoids sargasilols B–I (2–9), were isolated from a China Sea collection of the brown alga Sargassum siliquastrum, together with six known analogues (10–15). The structures of the new chromanes were identified by extensive spectroscopic analysis and by comparison with previously reported data. Compounds 1–3 and 6–15 exhibited inhibition against LPS-induced NO production in BV-2 microglial cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…20–23 The increased oxidative stress and decreased acetylcholine (ACh) were believed to be critical factors in the development of AD. 24–27 To establish the appropriate experimental concentration of the four compounds, a CCK-8 kit was adopted to detect the BV2 cell viability. The results showed that the four compounds at 3.125, 6.25, 12.5, 25, and 50 μM have no toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…20–23 The increased oxidative stress and decreased acetylcholine (ACh) were believed to be critical factors in the development of AD. 24–27 To establish the appropriate experimental concentration of the four compounds, a CCK-8 kit was adopted to detect the BV2 cell viability. The results showed that the four compounds at 3.125, 6.25, 12.5, 25, and 50 μM have no toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Western-blot assay was established referred to previously reported protocols [ 20 ]. Briefly, PC12 Cells were seeded in 6-well plates at a density of 4 × 10 5 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded on cell slides and placed in 24-well plates at a number of 1 × 10 5 cells per well and then processed as described [ 20 ]. After treatments with drugs, the cells were fixed with paraformaldehyde, blocked with goat serum, incubated with an anti-Nrf2 antibody overnight, and then with a secondary antibody for 1 h in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation